STUDI TENTANG MANAJEMEN ATLET PANAHAN PADA ALTIUS SINGAPERBANGSA ARCHERY CLUB KARAWANG DARI TAHUN 2016 SAMPAI 2019 - aria Kusuma Yuda; Rhama Nurwansyah S; Citra Resita (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
ABSTRACT The purpose of this study is to find out that : (1) athlete coaching on Altius Singaperbangsa  Archery Club Karawang from the year of 2016 to 2019. (2) Facilities and infrastructure of Altius Singaperbangsa  Archery Club Karawang from the year of 2016 to 2019. (3) Training program of Altius Singaperbangsa  Archery Club Karawang from the year of 2016 to 2019. (4) the achievements of Altius Singaperbangsa  Archery Club Karawang from the year of 2016 to 2019. This study used qualitative descriptive method. Case study strategy is used within this study, that is the target to be examined has been limited and determined, and focused on one location that has its own characteristic. The data used is the source of objects, places, events, active club sources, and documents. Data were collected by observation, interview, and document analysis techniques.The sampling used are purposive and snowball  sampling, that is sampling based on research puspose, where the researcher choose the sources who are considered knowing the problem deeply and can be trusted, and can be developed after the field reasearch. In this research, two triangulation techniques are used to find the data validity, that is data triangulation and method triangulation. The data analysis technique used by the researcher is qualitative descriptive technique, by using the collected data then compiled for analysis so that the researcher could get an overview of the researched variables. Based on the results of this study, the conclusions obtained are : (1) The coaching has been done by Altius Singaperbangsa Archery Club Karawang is good enough, cause fo the coach is able to do the achievement coaching in practicing, both in and outside the club hours. (2) Facilities and infrastructure that owned and used by Altius Singaperbangsa Archery Club Karawang are still not good enough, so that can’t support the running of activities maximally. (3) The training programm done by Altius Singaperbangsa Archery Club Karawang are still not good enough is good enough, because the training given were ordinary daily exercise for everyday and programmed in the short, medium, and long term. (4) Development achievements that have been reached by the athletes of Altius Singaperbangsa  Archery Club Karawang at the regency and provincial level from the year 2016 to 2019 are good enough